Educational gradient in dental caries - Moltubakk, Silje Navjord (UiT Norges arktiske universitet, 2022)
Background: Dental health is an important aspect and a key indicator of general health. However, detailed data on dental health in the adult population in Norway is lacking. Literature indicates that people with lower socioeconomic position (SEP) have significantly poorer dental health than people with higher SEP. For example, adults in Norway with higher education report better self-reported dental health status compared with adults who have lower education. Therefore, although the inequality in dental health has been significantly reduced in Norway the last 50 years, findings may indicate that there still exists inequality in dental health among adults in Norway. These inequalities often manifest in a gradient. Aim: This study sought to investigate if educational gradient in dental caries exists in the adult population in Tromsø municipality. The objective was to assess an association between educational level and dental caries experience among the participants of the Tromsø 7 study. Materials and methods: The study population consisted of 3823 adults living in Tromsø municipality in northern- Norway who participated in the Tromsø 7 study. Social determinants: education, age, sex, household income, spouse, childhood financial situation, mother and fathers’ education, siblings, and intermediary determinants: smoking, alcohol consumption, exercise, soft drinks, tooth brushing, fluoride toothpaste, interdental cleaning aids, fluoride tablets, fluoride rinse, dental care and dental satisfaction was self-reported in a questionnaire. Registration of decayed, missing, filled, teeth (DMFT) score was performed after the clinical examinations by calibrated dentists using bitewing radiographs and intra-oral clinical photographs. Descriptive statistics, chi- square test and independent t-test was performed to describe the sample. Univariable and multivariable binary logistic regression models were conducted and the association between educational level and DMFT score was adjusted for selected social and intermediary ...